Assessing urban disaster waste management requirements after volcanic eruptions. (January 2021) - Hayes, Josh L.; Wilson, Thomas M.; Brown, Charlotte; Deligne, Natalia I.; Leonard, Graham S.; Cole, Jim
Abstract: Disasters can generate substantial quantities of disaster waste that must be managed for effective response and recovery. Modelling the potential quantities and types of waste expected after disasters has been widely applied for a variety of hazards (e.g., earthquake, hurricane, flood, tsunami). However, there has been limited consideration of modelling disaster waste as a result of volcanic eruptions, which can generate considerable disaster waste volumes and management issues. In this work we develop a modelling framework for assessing disaster waste types and quantities after volcanic eruptions affecting urban environments. The framework facilitates quantification of different waste types resulting from damaged buildings and classification of different clean-up zones. The framework is based on vulnerability models and heuristic analysis of the likely waste generated at different damage states from volcanic hazards and is designed to be applied as part of a standard risk modelling procedure. Clean-up zone classifications are developed by identifying key management requirements for different urban land use types. We apply the framework to a case study, using eight eruption scenarios for the Auckland Volcanic Field, New Zealand. Modelling outputs indicate that building debris waste generated under each of these scenarios is likely to be on the order of hundreds of thousands to tens of millions of tonnes. Waste is also likely to be highly mixed in some areas where buildings are heavily damaged and contaminated with volcanic products such as tephra and/or lava, which will complicate disaster waste management activities.